Towards the Problem of Forming Full Strength Welded Joints on Aluminum Alloy Sheets. Part II: AA7475; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Kalashnikova T. Tatiana; Tarasov S. Yu. Sergei Yulievich; Eliseev A. Alexander; Fortuna A. Anastasiya (2016, 2016)
Title screen